In memoriam - CPH 26(2) (Czasopismo Prawno-Historyczne, 1974)
Witold Sawicki 1904-1973 (Wojciech Szwarc) ... 279 Bibliografia prac naukowych Doc. Dra Witolda Sawickiego (Marian L. Klementowski) ... 284 Borys Łapicki 1889-1974 (Jan Kodrębski) ... 287 Györgi Diósdi 1834-1973 (Henryk Kupiszewski) ... 289